2022
DOI: 10.3390/v14081706
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficacy and Safety of Anti-Viral Agents for Non-Hospitalized Patients with COVID-19: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials

Abstract: This network meta-analysis compared the clinical efficacy and safety of anti-viral agents for the prevention of disease progression among non-hospitalized patients with COVID-19. PubMed, Embase, Web of Science, Cochrane Library, ClinicalTrials.gov and the WHO International Clinical Trials Registry Platform were searched from their inception to 28 May 2022. Only randomized controlled trials (RCTs) that investigated the clinical efficacy of anti-viral agents for non-hospitalized patients with COVID-19 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 21 publications
1
38
0
2
Order By: Relevance
“…Both clinical trials and real-world study suggest the benefits of both oral antivirals in reducing hospitalization and mortality [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In a systemic review and meta-analysis, treatment with both NMV-r and MOV were associated with a significantly lower risk of COVID-19 related hospitalization or death compared with the placebo, with the benefits being more pronounced for NMV-r than MOV [ 20 ]. A real-world study in Italy suggested both NMV-r and MOV to be effective, while patients treated with NMV-r had lower risk of hospitalizations and earlier recovery, though the age, body mass index and underlying co-morbidities differed in the NMV-r and MOV groups, as in our study as well as other real-world studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical trials and real-world study suggest the benefits of both oral antivirals in reducing hospitalization and mortality [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In a systemic review and meta-analysis, treatment with both NMV-r and MOV were associated with a significantly lower risk of COVID-19 related hospitalization or death compared with the placebo, with the benefits being more pronounced for NMV-r than MOV [ 20 ]. A real-world study in Italy suggested both NMV-r and MOV to be effective, while patients treated with NMV-r had lower risk of hospitalizations and earlier recovery, though the age, body mass index and underlying co-morbidities differed in the NMV-r and MOV groups, as in our study as well as other real-world studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, molnupiravir, nirmatrelvir, remdesivir, and paxlovid have demonstrated neutralizing activity against variants, including Omicron [ 6 , 45 ]. Lai et al reviewed and analyzed data from RCTs to determine the clinical efficacy and safety of antiviral drugs for non-hospitalized COVID-19 patients [ 47 ]. Their results indicated that antiviral drugs were related to a significantly lower risk of hospitalization/death [ 47 ].…”
Section: Current Treatments For Covid-19mentioning
confidence: 99%
“…Lai et al reviewed and analyzed data from RCTs to determine the clinical efficacy and safety of antiviral drugs for non-hospitalized COVID-19 patients [ 47 ]. Their results indicated that antiviral drugs were related to a significantly lower risk of hospitalization/death [ 47 ]. Additionally, nirmatrelvir plus RTV was the best antiviral treatment with the lowest hospitalization/death risk, followed by remdesivir and molnupiravir [ 47 ].…”
Section: Current Treatments For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…As per the studies, oral nirmatrelvir plus ritonavir and intravenous remdesivir is reported to be the better choice, followed by molnupiravir. However, most of these drugs just target the early steps of the life cycle or the early phase of infection, and there are no excellent drugs that provide a long-lasting suppression of viral replication [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%